Effect of insect-proof net house on flowering and seeds quality of cucumber (Cucumis sativus) - Kumar, Mukul; Sirohi, H S; Singh, Balraj; Tomar, B S; Singh, A K (The Indian Journal of Agricultural Sciences, 2020)
An experiment was carried out during kharif 2013-14 under insect proof net house and open field at Centre for Protected Cultivation Technology, IARI, New Delhi and CCR (PG) College, Muzaffarnagar (UP) in Cucumber cv. (Pant Sankar Khira-1). Opening of first female and male flower in seed and pollen parents (39.0 and 34.90 days) was significantly lower under insect proof net house compared to open field condition (44.15 and 41.37 days). The production of number of female and male flowers (25.42 and 36.57) in seed and pollen parents was significantly higher under insect proof net house compared to open field condition (8.81 and 18.16). Seed length was significantly higher under insect proof net house (11.32 cm) in compared to open field condition (10.36 cm). Seed width(mm), seed coat weight(mm), cotyledon weight(g) and 100 seeds weight(g) were also significantly higher under insect proof net house (4.11, 0.13, 0.13 and 3.48 respectively) than open field condition (3.39, 0.10, 0.14 and 2.59, respectively). The germination percentage, seedling length, vigour index I and II also exhibited the same trend being significantly higher under insect proof net house (87.21, 31.43 cm, 2825.54 and 11.08, respectively) compared to open field condition (82.02, 26.38 cm, 2224.83 and 7.62, respectively). Electrical conductivity was lower under insect proof net house (11.22) but higher in open field condition (12.03).